Cultivating Spiritual Intelligence for a participatory worldview: The contribution of Archetypal Cosmology - Zappalà, Gianni (Journal for the Study of Spirituality, 2021)
Humanity finds itself in a collective liminal space between worldviews, on a trajectory from a dominant scientific materialism towards a participative worldview informed by a spiritual and archetypal consciousness. This paper suggests that Spiritual Intelligence (SQ), the cognitive ability to find higher meaning, value, and purpose in life through transcending rational intelligence may help to birth and reinforce the emerging worldview. The dominant modes of thinking embedded within educational institutions, however, remain within the confines of the mechanistic-materialist model. Nurturing SQ requires multiple ways of knowing, a pedagogy based on engaging the head, heart and accessing our inner experience and intuitive voice. This paper identifies one recent expression of a participative worldview - Archetypal Cosmology - that is not only consistent with post-materialist views of consciousness but can also contribute to cultivating and developing SQ. Archetypal Cosmology is based on an enchanted cosmos in which the microcosm of the psyche is reflected in the macrocosm of the universe through a mysterious yet empirically observable planetary synchronicity. After reviewing the key tenets of SQ and Archetypal Cosmology, the paper: (i) highlights a correspondence between the principles of SQ and the planetary archetypal meanings suggesting that SQ may be a type of Archetypal Intelligence; (ii) illustrates how Archetypal Cosmology provides another mode to cultivate SQ; (iii) suggests that the synthesis of SQ and Archetypal Cosmology, both multi-sensory ways of knowing that include the imaginal, symbolic, mythical and spiritual, may help bring about new modes of thinking to bridge the sciences and humanities.